2007
DOI: 10.4049/jimmunol.179.11.7523
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of Bcl-xL or Bcl-2 by Murine B Cells Enhances the In Vivo Antipolysaccharide, but Not Antiprotein, Response to IntactStreptococcus pneumoniae

Abstract: IgG antipolysaccharide (PS) and antiprotein responses to Streptococcus pneumoniae (Pn) are both CD4+ T cell dependent. However, the primary IgG anti-PS response terminates more quickly, uses a shorter period of T cell help, fails to generate memory, and is more dependent on membrane Ig (mIg) signaling. We thus determined whether this limited anti-PS response to Pn reflected a greater propensity of PS-specific B cells to undergo apoptosis. We used mice that constitutively expressed the antiapoptotic protein Bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 76 publications
(72 reference statements)
2
36
0
Order By: Relevance
“…The propensity of particulate Ags to be sequestered within the marginal zone (MZ) (28), and the observation that MZBs in relation to FB are programmed to favor plasma cell over memory cell differentiation (22), led us to hypothesize that the failure of intact Pn to generate PPS14-specific IgG memory was secondary to its selective usage of MZBs to generate this response. Indeed, we show that the PPS14-specific IgG response to intact Pn14, but not conjugate, is markedly reduced in Lsc Ϫ/Ϫ mice, in which MZBs are defective in migrating from the MZ and are thus unable to receive CD4 ϩ T cell help (7,10). These data strongly suggest that intact Pn and soluble conjugate differentially utilize MZBs and FBs, respectively, to generate the PPS14-specific IgG response.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The propensity of particulate Ags to be sequestered within the marginal zone (MZ) (28), and the observation that MZBs in relation to FB are programmed to favor plasma cell over memory cell differentiation (22), led us to hypothesize that the failure of intact Pn to generate PPS14-specific IgG memory was secondary to its selective usage of MZBs to generate this response. Indeed, we show that the PPS14-specific IgG response to intact Pn14, but not conjugate, is markedly reduced in Lsc Ϫ/Ϫ mice, in which MZBs are defective in migrating from the MZ and are thus unable to receive CD4 ϩ T cell help (7,10). These data strongly suggest that intact Pn and soluble conjugate differentially utilize MZBs and FBs, respectively, to generate the PPS14-specific IgG response.…”
Section: Discussionmentioning
confidence: 69%
“…8), radically changes the nature of the in vivo IgG anti-PPS14 response relative to both purified capsular PPS14 as well as intact Pn. Thus, the IgG anti-PPS14 response to soluble PPS14-PspA conjugate is largely similar to the IgG anti-PspA responses to both conjugate and intact Pn14, including prolonged primary kinetics of induction and the generation of a CD4 ϩ T cell-dependent, PPS14-specific IgG memory response (7,9). Collectively, these data indicate that PPS14 in association with intact Pn14 is immunologically distinct from a soluble covalent conjugate of PPS14 and an immunogenic pneumococcal protein, despite the CD4 ϩ T cell dependence of the IgG responses to both immunogens.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies using intact heat-killed S. pneumoniae and a soluble pneumococcal conjugate vaccine strongly suggested that PS-specific IgG responses were derived from marginal zone and follicular B cells, respectively (18,19), with elicitation of distinct idiotypes on the PS-specific (serotype 14) IgG (17). Indeed, mice primed with intact serotype 14 S. pneumoniae do not elicit an augmented PS-specific IgG response following booster immunization with a soluble type 14 pneumococcal conjugate vaccine, in which the carrier protein is pneumococcal surface protein A (33), but do elicit an augmented response following booster immunization with intact GBS-III expressing type 14 PS (21).…”
Section: Mice Primed With Either Menc or A Soluble Conjugate Of Mcps-mentioning
confidence: 99%
“…For example, systemic immunization with intact S. pneumoniae induced PS-specific IgG that derived from splenic marginal zone B cells and expressed a distinct idiotype, whereas a pneumococcal conjugate vaccine of the same PS serotype (type 14) induced PS-specific IgG largely lacking this idiotype and derived from splenic follicular B cells (17)(18)(19).…”
mentioning
confidence: 99%